The Strategic Role of Reverse Logistics in Digital Commerce: A Narrative Review - Setiadi (Logistica : Journal of Logistic and Transportation, 2025)
The rapid expansion of e-commerce has heightened the significance of reverse logistics, with product return rates reaching up to 30% in some sectors. This study provides a narrative review that synthesizes current research on the trends and challenges of reverse logistics in e-commerce. Literature searches were conducted across multiple databases, including Scopus, Web of Science, Google Scholar, IEEE Xplore, and PubMed, using targeted keywords such as reverse logistics, e-commerce returns, supply chain sustainability, circular economy, and returns management. Inclusion criteria emphasized peer-reviewed studies published between 2015 and 2025. The findings reveal that technological innovations, particularly artificial intelligence, blockchain, and the Internet of Things, are central to improving efficiency and transparency in return processes. Economically, reverse logistics imposes significant costs on firms. At the same time, it offers opportunities for profitability through outsourcing and predictive analytics. Environmentally, returns exacerbate carbon emissions and waste, particularly in the fashion sector, necessitating sustainable packaging and circular economy practices. Customer perspectives highlight the importance of return policies and service experiences in shaping loyalty and trust. Discussion further indicates that systemic barriers, including regulatory gaps and infrastructural challenges, limit effective adoption, particularly in developing regions. The review concludes that coordinated policy measures, technological adoption, and customer-centric strategies are critical for advancing sustainable and efficient reverse logistics. Future research should explore the intersection of technology, policy, and consumer behavior to strengthen reverse logistics as a driver of both profitability and sustainability,